(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The study is based on the attempt to understand the scene of the lorica of a headless statue of the probable end of the Claudian age, found in the archaeological area of Rusellæ (Roselle, GR) in a structure connected to the imperial cult. The analized decoration is made up of different components: an arms trophy and an eagle in almost central position, while on their sides human figures are disposed, interpretable as barbarians and for which the identification with the Britain Caratacus is suggested: he is accompanied by his relativies, while he is addressing a supplication of freeing to the Senate and to the Emperor Claudio, according to the episode reported in Tacitus’ Annales (12.33-40).